Similar Antibody Responses Against Severe Acute Respiratory Syndrome Coronavirus 2 in Individuals Living Without and With Human Immunodeficiency Virus on Antiretroviral Therapy During the First South African Infection Wave. (2nd September 2021) - Snyman, Jumari; Hwa, Shi Hsia; Krause, Robert; Muema, Daniel; Reddy, Tarylee; Ganga, Yashica; Karim, Farina; Leslie, Alasdair; Sigal, Alex; Ndung'u, Thumbi; ,
Abstract: Background: There is limited understanding of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pathogenesis in African populations with a high burden of infectious disease comorbidities such as human immunodeficiency virus (HIV). The kinetics, magnitude, and duration of virus-specific antibodies and B-cell responses in people living with HIV (PLWH) in sub-Saharan Africa have not been fully characterized. Methods: We longitudinally followed SARS-CoV-2–infected individuals in Durban, KwaZulu-Natal, South Africa, and characterized SARS-CoV-2 receptor-binding domain-specific immunoglobulin (Ig) M, IgG, and IgA weekly for 1 month and at 3 months post-diagnosis. Thirty of 72 (41.7%) were PLWH, 25/30 (83%) of whom were on antiretroviral therapy (ART) with full HIV suppression. Plasma neutralization was determined using a live virus neutralization assay, and antibody-secreting cell population frequencies were determined by flow cytometry. Results: Similar seroconversion rates, time to peak antibody titer, peak magnitude, and durability of anti–SARS-CoV-2 IgM, IgG, and IgA were observed in people not living with HIV and PLWH with complete HIV suppression on ART. In addition, similar potency in a live virus neutralization assay was observed in both groups. Loss of IgA was significantly associated with age (P = .023) and a previous diagnosis of tuberculosis ( P = .018). Conclusions: Similar antibody responses and neutralization potency in people not living with HIV and PLWH on stable ART in an African setting suggest that coronavirus disease 2019 (COVID-19) natural infections may confer comparable antibody immunity in these groups. This provides hope that COVID-19 vaccines will be effective in PLWH on stable ART. Abstract : In a longitudinal study during the first COVID-19 infection wave in South Africa, we report no differences in anti-SARS-CoV-2 immunoglobulin M (IgM), IgG, and IgA antibody kinetics, peak titers, and neutralization in people living with HIV versus people without HIV.